Accidental and intentional exporters : comparing Indonesian and Malaysian MSMEs - Tham, Siew Yean; Tambunan, Tulus, 1956- (Singapore : ISEAS-Yusof Ishak Institute, 2019)
Regardless of the size of the domestic economy, there are ample reasons for firms to extend their markets beyond home shores. These include increasing sales, improving profits, diversifying risks, reaping economies of scale, matching the moves of competitors, enhancing competitiveness or accessing government incentives. Both Indonesia and Malaysia seek to enhance the competitiveness of their micro, small and medium enterprises (MSMEs) by including internationalization goals in their respective national development plans for these enterprises. Findings from fourteen case studies in the two countries indicate that exporting may be a serendipitous discovery, as few of these cases were born global in intent. Shifting to intentional exporting will require entrepreneurs to tap into government and/or private networks and thus connect with international buyers. Indonesian MSMEs are more inclined to depend more on government than private networks as they perceive the former to be more credible. Malaysian cases indicate some firms prefer private to government networks. This is attributed to the differences in the political economy of the two countries. Going forward, both countries need to consolidate their government-run programmes and reduce the fiscal burden. MSMEs should tap more into private networks to bridge the information gap that hinders their access to external markets. ASEAN can facilitate the entry of MSMEs into the ASEAN market by implementing resolutely current plans to reduce technical barriers to trade.
Title from publisher's bibliographic system (viewed on 20 Feb 2019).
Keywords: Small business -- Government policy -- Indonesia; Small business -- Government policy -- Malaysia; Export marketing -- Indonesia; Export merketing -- Malaysia